Meningkatkan Kualitas Pelayanan Terhadap Kepuasan Pelanggan dengan Metode SERVQUAL di CV. Budidaya Jamur Sejati - Zahro, Fatimatu; Riyana, Iis; Sulistyowati, Enik (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
To improve the quality of service towards customer satisfaction at CV.Budidaya Jamur Sejati using the SERVQUAL method. The study was conducted by distributing questionnaires to customers to measure their perceptions and expectations of the five dimensions of service quality, namely Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The results of the analysis showed that there was a negative gap in all dimensions of SERVQUAL, indicating that the service provided had not fully met customer expectations. The Assurance dimension showed the largest gap, indicating a need for improvement in the aspect of guaranteeing professionalism and staff skills. While the Tangibles dimension had the smallest gap, but still required attention. It can be concluded that it is necessary to improve employee competence, accelerate physical facility repair services, increase empathy towards customers, and conduct periodic evaluations to improve customer satisfaction and strengthen the position of CV.Budidaya Jamur Sejati in the mushroom cultivation industry in Indonesia.